Progesterone‐driven local regulatory T cell induction does not prevent fetal loss in the CBA/J×DBA/2J abortion‐prone model. (March 2017) - Schumacher, Anne; Dauven, Dominique; Zenclussen, Ana C.
Abstract : Problem: Best known for its endocrine and immunologic properties, progesterone (P4) is a pivotal player for pregnancy success. However, the immunologic actions underlying P4 protection are not completely understood. Here, we investigated whether P4 application in a murine abortion‐prone combination regulates regulatory T cells (Treg) and dendritic cells (DCs) and thereby affects pregnancy outcome. Method of study: Progesterone or vehicle was applied to DBA/2J‐mated CBA/J abortion‐prone animals in early pregnancy. On gestation day 10, peripheral and local DC and Treg numbers were analyzed and pregnancy outcome was determined. Results: Progesterone application provoked a significant increase in the uterine Treg pool but did not alter the abortion rate. Moreover, no significant changes could be observed in peripheral Treg levels and DC numbers after P4 application. Conclusions: Our findings suggest that P4‐induced local Treg elevation is not sufficient to overcome fetal rejection in this specific model of disturbed fetal tolerance.